Translation, cultural adaptation and validation of a patient‐reported experience measure for children - Anna Nordlind; Agneta Anderzén‐Carlsson; Ann‐Sofie Sundqvist; Karin Ängeby; Jo Wray; Geralyn Oldham; Ann‐Charlotte Almblad (Wiley, 2024)
Abstract Background There is no national, validated, generic patient‐reported experience measure (PREM) for children under 15 years of age in Sweden. A recent cross‐sectional study found no consensus in how children's voices are heard in paediatric health care, as well as a lack of validated questionnaires. Aim The aim of this study is to translate, adapt and validate the six versions of the Children's and Young People's PREM for use in a Swedish health care context. Design An exploratory sequential mixed‐method design including cognitive interviews and content validity index (CVI) was used. The interviews focused on evaluating children's understanding of the questionnaire, and the CVI was used to further adjust the relevance of the questionnaire. Participants A convenience sample of 62 children participated in the cognitive interviews and an additional convenience sample of 42 children was included in the CVI testing. The children, aged 8-16 years, were attending routine visits at paediatric departments in a county hospital and a children's hospital in the mid‐Sweden region between October 2020 and June 2022. Results The translation, adaptation and validation process identified several issues regarding the understanding of the questionnaire in a Swedish context. Adaptations were made based on issues related to context, wording and the structure of the questions. CVI testing resulted in the removal of 3-10 questions in each of the different versions of the questionnaire. Conclusion The study has resulted in six face‐ and content‐validated Swedish versions of the questionnaire ready for pilot testing. Although the versions of the original questionnaire were developed in collaboration with children in the United Kingdom, this did not mean that they could automatically be used in a Swedish health care context. This study confirms the importance of a rigorous process of adaptation and validation to ensure quality and applicability to children accessing health care in different countries. Patient or Public Contribution Children's views have guided the development of the original instrument and its adaptation to the Swedish health care context. Due to the strong patient involvement in the process of developing the Swedish versions of the questionnaire, the research group made a pragmatic decision to have no other patient contribution in the study.